2021
DOI: 10.1186/s12887-021-02643-x
|View full text |Cite
|
Sign up to set email alerts
|

Preconceptional and prenatal exposure to diurnal temperature variation increases the risk of childhood pneumonia

Abstract: Background Pneumonia is the leading cause of death and hospitalization among young children worldwide, but its risk factors remain unclear. Objective To evaluate the effect of maternal exposure to diurnal temperature variation (DTV) during preconceptional and prenatal periods on childhood pneumonia. Methods A retrospective cohort study by case-control design was conducted for pneumonia (N = 699) and no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
10
2
Order By: Relevance
“…Direct temperature exposure during the postnatal period could act on the respiratory system as well as on risk factors (eg, allergens) of altered lung function. 12 Contrary to previous research, 14,18,19,37 female newborns appeared more sensitive to both cold and heat than male newborns. However, previous studies 23,38 were performed on older populations and considered different lung function measurements.…”
Section: Biological Pathwayscontrasting
confidence: 74%
See 2 more Smart Citations
“…Direct temperature exposure during the postnatal period could act on the respiratory system as well as on risk factors (eg, allergens) of altered lung function. 12 Contrary to previous research, 14,18,19,37 female newborns appeared more sensitive to both cold and heat than male newborns. However, previous studies 23,38 were performed on older populations and considered different lung function measurements.…”
Section: Biological Pathwayscontrasting
confidence: 74%
“…20 In addition, male and female populations show differences in lung growth and airway development, [21][22][23] lending support to differential responses to environmental stressors. 14,18,19 This finding paves the way for the investigation of sex-specific critical windows of susceptibility. We leveraged lung function measurements performed in newborns of the SEPAGES (Suivi de l'Exposition à la Pollution Atmosphérique durant la Grossesse et Effets sur la Santé [Assessment of Air Pollution Exposure During Pregnancy and Effect on Health]) mother-child cohort and a cutting-edge spatiotemporal model of ambient temperature exposure combined with distributed lag models to explore the associations between prenatal and postnatal long-term and short-term temperature exposures and male and female newborn lung function.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…For instance, a prospective cohort study conducted in China among 2598 children found that prenatal exposure to diurnal temperature variation was signi cantly associated with the incidence of pneumonia in children aged 3-6 years (Miao, et al 2017). Similarly, Lu et al carried out a cohort study and discovered that childhood pneumonia was signi cantly associated with increased exposure to diurnal temperature differences throughout the entire pregnancy (Zheng, et al 2021). Apparently, the results of these studies suggest that extreme AT during pregnancy is associated with the risk of respiratory disease in the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal exposure to harmful environmental factors could harm organ development as well as infancy growth and could increase the risk of respiratory diseases in childhood (Gluckman, et al 2008). A study suggested that prenatal exposure to diurnal temperature variation plays an important role in the development of childhood pneumonia (Zheng, et al 2021). Also, the common cold in children was associated with prenatal exposure to air temperature variation (Lu, et al 2018).…”
Section: Introductionmentioning
confidence: 99%